THE INFLUENCE OF BITTER EXTRACT (Andrographis paniculata Ness.) ON URIC ACID LEVEL OF MICE (Mus musculus L.) MALE - Winda Wulandari (Serambi Biologi, 2018)
Background this study was to examine the influence of extract of bitter against levels of uric acid in mice. The purpose of this research is to know the influence of extract of bitter (Andrographis paniculata Ness.) against the levels of uric acid house mouse (Mus musculus l.)  males. This type of research is research experiments using Completely Randomized Design (CRD), which consists of 4 treatments and 5 replicates. This research procedure is the preparation of the implementation phase, research and observations. This research procedure is the preparation of the implementation phase, research and observations. Observation data were analyzed by ANOVA (Analisis of Varians) test and if there were significant differences then continued with the DNMRT (Duncan New Multiple Range Test) further test on significance 5 %. The results showed that the levels of uric acid house mouse (Mus musculus l.) males at the basal data changes after the and before the given sambiloto. The male MICE are naturally conditioned in a State of hiperurisemia with penginduksian compound containing high levels of purin. Based on the results of the study it can be concluded that the administration of bitter extract (Andrographis paniculata Ness.) significantly affected the decrease of uric acid levels in male mice (Mus musculus L.) in treatment 3 (P3) at a dose of 0.6 mg / BB mice.